Biosensing strategies based on enzymatic reactions and nanoparticles. Issue 8 (19th March 2018) - Díez-Buitrago, Beatriz; Briz, Nerea; Liz-Marzán, Luis M.; Pavlov, Valeri
Abstract : Application of new nanomaterials to detection of enzymatic activities allows the development of new sensitive and selective bioanalytical assays based on enzymes for recognition and signal amplification. Abstract : Enzymes are pivotal elements in bioanalysis due to their specificity and extremely high catalytic activity. The sensitivity of bioanalytical assays depends mainly on the capacity of an observer to detect the product(s) of a biocatalytic reaction. Both natural and artificial compounds have been traditionally used to evaluate enzymatic activities. The drawbacks of chromogenic and fluorogenic organic enzymatic substrates are their high cost and low stability, resulting in high background signals. We review here state of the art assays in the detection of enzymatic activities using recent advances in nanoscience. Novel methods based on the use of nanoparticles lead to increased sensitivity and decreased costs for bioanalysis based on enzymes as recognition elements and signal amplifiers in Enzyme-Linked Immunosorbent Assays (ELISA). Novel approaches toward the detection of enzymatic activities are based on biocatalytic synthesis, modulation, etching, and aggregation of nanoparticles under physiological conditions.